2020
DOI: 10.3390/cryst10090794
|View full text |Cite
|
Sign up to set email alerts
|

The Crystallization Behaviors of SiO2-Al2O3-CaO-MgO-TiO2 Glass-Ceramic Systems

Abstract: To evaluate the crystallization behavior of Ti-bearing blast furnace slag-based glass ceramics, SiO2-Al2O3-CaO-MgO-TiO2 systems with various TiO2 were investigated. The crystallization process and mechanical properties were analyzed. The results show that with TiO2 increasing, exothermic peak temperature (Tp) decreases, and the crystallization is promoted by the introduction of TiO2. A small amount of TiO2 (≤4%) addition can significantly promote crystallization, and when TiO2 continues to increase, the crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The variation of the Gibbs free energy with temperature for reactions (5-7) is shown in Figure 8. It can be found that the standard Gibbs free-energy changes of reaction ( 5) and ( 6) is smaller than that of reaction (7), meaning that CaO prefers to react with SiO 2 rather than TiO 2 in the presence of Al 2 O 3 and MgO. Besides, it can be obtained that the increasing the SiO 2 content will promote the formation of Ca 2 MgSi 2 O 6 and inhibit the formation of CaTiO 3 .…”
Section: The Crystallization Phase Composition Of Micro-crystal Stonesmentioning
confidence: 94%
See 2 more Smart Citations
“…The variation of the Gibbs free energy with temperature for reactions (5-7) is shown in Figure 8. It can be found that the standard Gibbs free-energy changes of reaction ( 5) and ( 6) is smaller than that of reaction (7), meaning that CaO prefers to react with SiO 2 rather than TiO 2 in the presence of Al 2 O 3 and MgO. Besides, it can be obtained that the increasing the SiO 2 content will promote the formation of Ca 2 MgSi 2 O 6 and inhibit the formation of CaTiO 3 .…”
Section: The Crystallization Phase Composition Of Micro-crystal Stonesmentioning
confidence: 94%
“…Titanium‐bearing blast furnace slag is mainly produced by vanadium and titanium magnetite in the smelting process 4–6 . A large amount of titanium‐bearing slags is piled up randomly, which not only wastes resources, but also seriously threatens the environment 7,8 . Therefore, the disposal and reuse of titanium‐bearing slags have become a difficult issue 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glass-ceramics have been widely reported and are generally obtained by using heat treatment techniques to control the crystallization of glass samples. The literature indicates that glass-ceramics possess better mechanical performance and higher chemical and thermal stability than the parent glasses; in particular, the presence of regular nano-crystals is helpful to improving the properties of glass-ceramics [11][12][13]. However, iron phosphate glass-ceramics containing rare earth elements have received less attention [7,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the low Ti-bearing blast furnace slag can be a good candidate for the preparation of slag-based glass ceramics [22], where a small amount of TiO 2 in the Tibearing blast furnace slag can be the nucleating agent. In our previous work [23], the effects of TiO 2 on the crystallization behavior of Ti-bearing blast furnace slag-based glass ceramics were investigated. The results suggested that it was difficult to achieve threedimensional crystal growth and two-dimensional crystallization was shown in the sample with 2 wt% TiO 2 .…”
Section: Introductionmentioning
confidence: 99%